1989
DOI: 10.1002/app.1989.070381009
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the UV degradation of PVC window frames by microhardness analysis

Abstract: SynopsisWhile well-known methods of bulk analysis of thermal degradation of PVC become standard industrial tools, techniques for the study of surface damage produced by weathering are not generally considered. In this paper we present a new test, based on microhardness measurements, which can be used as a complementary technique for the study of this phenomenon. Comparison of this method with color changes and specific elongation at break measurement has been established for PVC window frames.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
1

Year Published

1990
1990
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 4 publications
0
16
0
1
Order By: Relevance
“…The mechanical properties and the colour get deteriorated due to the presence of oxygen and humidity [19,20]. So to prevent this weathering titanium dioxide and UV stabilizers are incorporated.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanical properties and the colour get deteriorated due to the presence of oxygen and humidity [19,20]. So to prevent this weathering titanium dioxide and UV stabilizers are incorporated.…”
Section: Introductionmentioning
confidence: 99%
“…53 Only small changes were detected because the core is not affected and the surface is continuously changed due to surface erosion process. 54 Impact strength readings are affected by the presence of a degraded layer on the surface of PVC materials. 54 Impact strength readings are affected by the presence of a degraded layer on the surface of PVC materials.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…For instance, the tensile strength of white poly(vinyl chloride), PVC, pipes exposed for 24 months in Dhahran (Saudi Arabia) decreased by 43% while an exposure of the same duration in Florida resulted in only a 26% decrease in the property [1]. Gonzalez et al [2] reported that one of the major problems associated with PVC is its sensitivity to weathering and UV irradiation. Furthermore, the presence of oxygen and humidity induces changes in its mechanical properties.…”
Section: Introductionmentioning
confidence: 97%